2022
DOI: 10.1111/jcal.12675
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between self‐regulated learning and learner behaviour in a massive open online course

Abstract: Background: Learners in Massive Open Online Courses (MOOCs) are presented with great autonomy over their learning process. Learners must engage in self-regulated learning (SRL) to handle this autonomy. It is assumed that learners' SRL, through monitoring and control, influences learners' behaviour within the MOOC environment (e.g., watching videos). The exact relationship between SRL and learner behaviour has however not been investigated.Objectives: We explored whether differences in SRL are related to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
(96 reference statements)
1
12
0
Order By: Relevance
“…These findings highlight the importance of considering factors affecting acceptance and willingness to engage in collaborative digital tools when implementing them in educational systems (Cheung & Vogel, 2013). Moreover, as mentioned above, the autonomy that is self‐inherent to the system suggests that students require self‐regulation learning skills to utilize the various functions (Jansen et al, 2022). When self‐regulation skills are underdeveloped or unsupported by the instructors, the effectiveness gained from using the hyper‐video system could be compromised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings highlight the importance of considering factors affecting acceptance and willingness to engage in collaborative digital tools when implementing them in educational systems (Cheung & Vogel, 2013). Moreover, as mentioned above, the autonomy that is self‐inherent to the system suggests that students require self‐regulation learning skills to utilize the various functions (Jansen et al, 2022). When self‐regulation skills are underdeveloped or unsupported by the instructors, the effectiveness gained from using the hyper‐video system could be compromised.…”
Section: Discussionmentioning
confidence: 99%
“…For example, instructors can implement directive questions within the videos, inviting students to answer and collaborate with each other (Mirriahi et al, 2021; Tseng, 2021). Such scaffolds were found to promote active and collaborative learning in digital collaborative learning environments (e.g., Shin, et al, 2020; Jansen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More precisely, mastery goal-orientation predicts a better use of SRL and supportive online behavior according to Yeh et al (2019) . Learning strategies themselves, specifically SRL strategies, are advantageous for online learning ( Yukselturk and Bulut, 2007 ; Jansen et al, 2022 ). This is supported by Steinkamp (2018) who found that a lack of organization and the ability to prioritize leads to struggling in online learning.…”
Section: Introductionmentioning
confidence: 99%
“…One of the crucial aspects of school learning and lifelong learning is self-regulation, which means that students who use appropriate self-regulation strategies may learn more (Núñez Perez et al, 2006;Badali et al, 2022;Biwer et al, 2022;Jansen et al, 2022;Shin and Song, 2022). A basic premise of self-regulated learning is that there are regulatory processes (i.e., monitoring and control) that are performed on aspects associated with school learning, and can be understood, fostered, and even trained for being transferred to other learning tasks (Bell and Kozlowski, 2008;Usher and Schunk, 2018).…”
Section: Introductionmentioning
confidence: 99%